Integration of HAZOP and Bayesian network in city gas explosion emergency response processes - Peng Gao; Weijun Li (Emergency Management Science and Technology, 2022)
City gas explosion accidents have occurred frequently in recent years, leading to major injuries and losses. An effective emergency response process is necessary to deal with city gas accidents by preventing them from expanding and reducing losses. However, emergency response is a complex process that includes many contributing factors, such as personnel, departments, and materials. If one or more of these factors fails, it will affect the implementation of the emergency response. Therefore, more efforts should be made on the systematic procedures and methods addressing risks in emergency response process. From the view of Process Hazard Analysis (PHA), the emergency response process can be seen as a work process with many operation nodes. In this sense, PHA methods such as HAZOP can be used for the risk analysis of the emergency response process. First, the emergency response process of a city gas explosion accident is broken down into procedure-based operations. Then HAZOP is used to comprehensively review the process and obtain deviations, causes, and consequences, which are considered as risk factors. Finally, Bayesian networks are used to characterize the inter relationships of various factors and quantify the risk of the emergency response process. Furthermore, the most critical events can be identified based on the sensitivity analysis. The results show that firefighters' operations, management of the emergency command center, and environmental conditions on site are critical factors during city gas explosion accidents. The method proposed can help identify potential risks of the emergency response process systematically and prevent accident expansion.